Método para identificar simultaneamente duas características elétricas moduláveis por parâmetros fisiológicos de microcircuitos RLC injetáveis - Oliveira, Raul José Fernandes de (2007)
This work proposes a biotelemetric method to determine simultaneously two electrical characteristics (modulated by physiological parameters) from a passive injectable RLC microcircuit. Due to the presence of free ions inside the biological tissue, inductive links (loop antennas) must be employed, instead of dipole antennas. As the coil of the sensor presents small dimensions (diameter of about mm) its magnetic coupling to the monitoring device requires special attention. To monitor the sensor, a digital device assembled with a group of coils to maximize the mutual inductance (at a distance of 5 mm) between them was developed, detecting its resonance frequencies and the respective amplitude (through a frequency sweep) in real-time. The electrical response acquired by the detector from the sensor was analytically modeled. The model indicates a time constant to consider for each change of the signal frequencies to prevent errors in the response. From that theoretical model, an equation to determine the total resistance from the RLC circuit was obtained and confirmed by experiments. Then, a method to determine the resonance frequency and the total resistance from remote RLC circuit was proposed. A sensor was developed to verify the accuracy and the limits from this method. A parallel RLC circuit was built inside a silicone rubber tube. When the tube is stretched, a ferrite rod assembled beside the inductor is displaced varying the resonance frequency and, changing the environmental temperature, a NTC varies the quality factor of the circuit. Tests using the proposed method to monitor the sensor were realized. Errors small than 0.57 % in the resonance frequencies and 0.77 % in the temperature were obtained. The measured influence of the temperature variation over frequency determination was less than 0.16 %, indicating that the method is feasible.